Architettura per la liturgia nelle chiese dell’occidente. Appunti di un liturgista - Jura, Piotr Pawel (Teologia i Człowiek, 2023)
Architecture for the Liturgy in the Western Churches: Notes from a Liturgist Virtually all religions have their spaces of worship. In fact, the very term “temple” derives from the Greek verb temno, “to cut off,” which points to a space that is cut off from the whole and dedicated to a deity. Likewise, after Christ’s resurrection, Christians would need a venue for ritual worship that would become a place of encounter with God the Trinity. That place would not be an equivalent of the Jewish or pagan temples, which were determined by the presence of a deity and considered sacred and sanctifying on account of that presence. A place of Christian worship would be identified mainly by action, that is, by the celebration of the misterium with Christ at its center. Here, Jesus in present by the power of His word. The faithful gather in His name when they are called to remember Him: “Do this in remembrance of me” (Luke 22:19) and “For where two or three are gathered in my name, there am I among them” (Matthew 18:20). In a temple, a meeting of the faithful was due to chance, whereas in a Christian place of worship, the meeting is integral to the sacred place itself. The individual believers are its living building stones, and the Holy Spirit is the unifying force that binds them together. In other words, for a Christian, there is no material place where God lives, and no place can contain Him. Over the years, the noun denoting a congregation of Christians, that is, ecclesia (“church”) was adopted to describe the place in which the congregation is taking place.